10m+11=4(2m+1)+3m

Simple and best practice solution for 10m+11=4(2m+1)+3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10m+11=4(2m+1)+3m equation:


Simplifying
10m + 11 = 4(2m + 1) + 3m

Reorder the terms:
11 + 10m = 4(2m + 1) + 3m

Reorder the terms:
11 + 10m = 4(1 + 2m) + 3m
11 + 10m = (1 * 4 + 2m * 4) + 3m
11 + 10m = (4 + 8m) + 3m

Combine like terms: 8m + 3m = 11m
11 + 10m = 4 + 11m

Solving
11 + 10m = 4 + 11m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11m' to each side of the equation.
11 + 10m + -11m = 4 + 11m + -11m

Combine like terms: 10m + -11m = -1m
11 + -1m = 4 + 11m + -11m

Combine like terms: 11m + -11m = 0
11 + -1m = 4 + 0
11 + -1m = 4

Add '-11' to each side of the equation.
11 + -11 + -1m = 4 + -11

Combine like terms: 11 + -11 = 0
0 + -1m = 4 + -11
-1m = 4 + -11

Combine like terms: 4 + -11 = -7
-1m = -7

Divide each side by '-1'.
m = 7

Simplifying
m = 7

See similar equations:

| 5y+11=5y+10 | | -x^2-2x+3=0 | | x^5+3x^4-5x^3+2x^2-7x+3=0 | | -7=-8Y+9 | | 6(2a+5)=-3a-45 | | 2(-1-3x)=-74 | | 27x^3+72x^2+48x= | | -x^2-22x-47=0 | | 53=-4(13+3) | | 8x+2y=12 | | -4k+16=4 | | 28x^2-13x=0 | | 9a+2b=10 | | -8a=2a+26-12a | | 60=7X-3 | | 3x+3y=15 | | t(10t+30)=180 | | 4x+18+2x=12 | | 2x^2-11x+13=0 | | 2*(3*x+3)-4*(5*x-3)=x*(-x-13)-x*(x-5) | | 2*(3x+3)-4*(5x-3)=x*(-x-13)-x*(x-5) | | 18x^2+10=-135 | | 2(3x+3)-4(5x-3)=x(-x-13)-x(x-5) | | 7x^2-2=61 | | 5(2x-3)+(x-7)=9x | | 7+5w=-18 | | 3m+5.7=-18.3 | | 4x^2=184 | | 25=11x-8 | | 3x-19=7x-3 | | 2i+3i=18 | | .40x-.20(50+x)=-.40(50) |

Equations solver categories